3D numerical model to investigate the rheological properties of basalt fiber reinforced asphalt-like materials. (1st May 2017) - Zhang, Xiaoyuan; Gu, Xingyu; Lv, Junxiu; Zou, Xiaoyong
Abstract: This paper presents a new three-dimensional (3D) numerical model to investigate the viscoelastic response and reinforcement mechanism of asphalt-like materials, including asphalt mastic and mortar mixed with basalt fibers at high temperature. For the 3D numerical model, basalt fiber reinforced asphalt-like materials (BFRA) are assumed to consist of two components: the homogeneous asphalt-like matrix with the Burgers viscoelastic model and the basalt fibers with the elastic model. The straight round basalt fibers are considered to be dispersed to random locations and orientations in the matrix, and a 3D algorithm is introduced to generate the numerical model in MATLAB software. The numerical model is then employed in a series simulations of the shear rheological and uniaxial compressive tests in ABAQUS software to study the rheological behavior and reinforcement effect of different fiber contents under constant loading. Results indicate that the rheological behaviors of the BFRA numerical model are in excellent agreement with the test results, and the reinforcement effect increases with the fiber contents within a certain range. Further numerical simulations are performed to analyze the effect of fiber aspect ratios, L D . Simulated results show that the decrease of L D has a positive effect on rheological behavior under a constant fiber diameter.